The “Ticas” of “Matema” of an African People: An exercise for the Brazilian Classroom. - Eliane Costa Santos (Revista Latinoamericana de Etnomatemática, 2008)
This article has as its central focus the examination of one of the ways that African culture can be introduced into the mathematics classroom, contributing to the transformation of this formal space of the classroom into an area in which culture is intertwined with scholarly knowledge through the transdisciplinarity of ethnomathematics. The thesis that permeates [this work] can be delineated as how African culture, through the representation of African Kente cloth looms, can contribute to the processes of teaching and learning in a mathematics classroom. The wefts are the theoretical references of Stuart Hall on culture and multiculturalism; D'Ambrosio on transdisciplinarity and ethnomathematics; Dennis on Kente cloth; and the weavers of Ghana on the technologies of Kente cloth. To find a general understanding, we locate Ghana on the African Continent, we quote the myths of the Kente looms, and finally, we present a proposal on how to create a transcultural connection between the knowledge of African culture and a mathematics classroom in Brazil.